Perftoran® Inhibits Hypoxia-Associated Resistance in Lung Cancer Cells to Carboplatin - Gamal-Eldeen, Amira M.; Alrehaili, Amani A.; Alharthi, Afaf; Raafat, Bassem M. (Frontiers in Pharmacology, 2022)
Perftoran® (perfluorodecalin) is an oxygen carrier, and carboplatin is a common chemotherapy drug used worldwide for lung cancer treatment. Hypoxia is one of the factors that induce resistance of lung cancer cells to carboplatin. This study explored the role of Perftoran®, as an oxygen carrier, in lowering the resistance of lung cancer cells to carboplatin through suppression of hypoxia pathway mediators. The effect of Perftoran® on the resistance of human lung cancer A549 cells to carboplatin was investigated through the evaluation of cytotoxicity by MTT, cell death mode by dual DNA staining, DNA damage by comet assay, DNA platination (DNA/carboplatin adducts) by atomic absorption spectroscopy, hypoxia degree by pimonidazole, HIF-1α/HIF-2α concentrations by ELISA, expression of miRNAs (hypoxamiRs miR-210, miR-21, and miR-181a) by qRT-PCR, and the content of drug resistance transporter MRP-2 by immunocytochemical staining. Results indicated that compared to carboplatin, Perftoran®/carboplatin decreased cell resistance to carboplatin by potentiating its cytotoxicity using only 45% of carboplatin IC50 and inducing apoptosis. Perftoran® induced DNA platination and DNA damage index in cells compared to carboplatin alone. Moreover, compared to treatment with carboplatin alone, co-treatment of cells with Perftoran® and carboplatin inhibited cellular pimonidazole hypoxia adducts, diminished HIF-1α/HIF-2α concentrations, suppressed hypoxamiR expression, and decreased MRP-2. In conclusion, Perftoran® inhibited resistance of lung cancer cells to carboplatin through the inhibition of both hypoxia pathway mediators and the drug resistance transporter MRP-2 and through the induction of DNA/carboplatin adduct formation.